MENYIBAK CITRA PEREMPUAN DALAM CERPEN “MARIA “ ( SEBUAH KAJIAN SASTRA FEMINISME ) - Mulyadi, Budi (Faculty of Humanities, Diponegoro University, 2018)
The title of this research is The image of women Maria’short story. The purpose of this paper is to explain how the short story writer describes the strugle of the women named Maria who struggles against gender injustice. This paper is research model that use literary review research model to collect the dataThe paper shows that The woman named Maria who became the rule main in this story is described as a strong women who always struggle to show that the women also have the power to live independenly without depen on man.In this short story maria is described as women who has interesting personality eventhough phsphysicallynot is described not so pretty. Maria has adult thinking, independent, strong principle, brave, loyal friend. Maria hates the view that the womenis is weak creature. Maria is a women who dare to fight the male domination. Maria is a women who are very loyal to husband